Model Eliminasi Kemiskinan melalui Democratic-Governance Approach Berbasis Local-Resources di Era Otonomi Daerah - Bambang Sugeng Dwiyanto (Jurnal Maksipreneur, 2011)
Poverty is one of the main issues of Indonesian's social problems. This problem of poverty has been getting worse since the time of local autonomy, which brought serious imbalance in-between regions. However this problem can actually be solved if local government designed and implemented comprehensive and serious policies to battle poverty. Especially with democratic-governance based policies, which based on local-resources and local-wisdoms. This research is focused onto local governments' effort in battling poverty. This research was done on two regions which acted as samples, the region of Kendal, and the region of Deli Serdang. Based on this research, it can be qualitatively shown that policies that conform to the approach of democraticgovernance, which based on region's local-resources and local-wisdoms, are considerably effective in helping the local governments in their effort of battling poverty in their regions.